2012
DOI: 10.7150/ijms.4276
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Mineral Composition of the Human Calcified Cartilage Zone

Abstract: As the connecting tissue between the hyaline articular cartilage and the subchondral bone, calcified cartilage zone (CCZ) plays a great role in the force transmission and materials diffusion. However, the questions that remain to be resolved are its mineral composition and organization. In this study, 40 healthy human knee specimens were harvested; first the CCZ was dissected and observed by Safranin O/fast green staining, then CCZ chemical characteristics were measured by using amino acid assay and X-ray diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 17 publications
1
78
0
2
Order By: Relevance
“…Additionally, recent findings indicated that the proportion of HAp as an inorganic compound in the calcified cartilage layer was ranked only second to that of subchondral bone [8]. In the present bilayered scaffold, the mineralised layer consisted of a mixture of ACECM and HAp while the non-mineralised layer consisted of ACECM alone.…”
Section: Discussionmentioning
confidence: 78%
“…Additionally, recent findings indicated that the proportion of HAp as an inorganic compound in the calcified cartilage layer was ranked only second to that of subchondral bone [8]. In the present bilayered scaffold, the mineralised layer consisted of a mixture of ACECM and HAp while the non-mineralised layer consisted of ACECM alone.…”
Section: Discussionmentioning
confidence: 78%
“…Calcified cartilage interdigitates with the subchondral bone, and the rough interface between the tissues combined with high stiffness [2] of the calcified cartilage provides mechanical stability and resistance against shear failure [3]. Calcified cartilage is a thin (100–200 µm thick [4•]) tissue, is metabolically active [5], consists of a large proportion of hydroxyapatite (~65 % [6]), and remodels with loading [7] and aging [8]. Lane et al [4•] has showed that calcified cartilage thickness decreases with age, from ~200 µm at about age 20, down to less than 100 µm by age 90.…”
Section: Introduction: Osteochondral Junctionmentioning
confidence: 99%
“…The main components of the calcified layer are calcium salts deposition without sGAG (27). The X-ray mean attenuation of the calcified layer was not considered in our study, and each proportion of non-calcified layers was chosen as the following proportion: superficial layer (15%), middle layer (55%) and deep layer (30%).…”
Section: Methodsmentioning
confidence: 99%
“…The calcified layer of the histological section images was not considered for their corresponding CT images. The non-calcified layers were outlined and separated from the deep layer by the tidemark, which was also the boundary between the deep layer and calcified layer (26,27), and distributed by the same proportion in CT images. The sGAG optical density of the entire cartilage and layered cartilage region was then calculated.…”
Section: Methodsmentioning
confidence: 99%